1985
DOI: 10.1139/f85-142
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in the Inshore Forage Fish of Lake Michigan

Abstract: Concerns have been expressed that increasing predatory pressure by salmonids may change the forage fish community of Lake Michigan. A decline in alewife (Alosa pseudoharengus), the major forage fish, would be a forewarning of such a change. Our 1973–82 surveys showed that alewife declined 86% in 1980–82; concurrently, rainbow smelt (Osmerus mordax) and yellow perch (Perca flavescens) increased threefold and fivefold, respectively. Spottail shiner (Notropis hudsonius) and trout-perch (Percopsis omiscomaycus) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…Most studies showed that alewives were the principal prey of Lake Michigan salmon (Eck and Wells 1983, Jude and Tesar 1985, and Jude et al 1987. The chances of overstocking salmon increased since the alewife population was decreasing, and there was increasing evidence that salmon were reproducing (Trudeau 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies showed that alewives were the principal prey of Lake Michigan salmon (Eck and Wells 1983, Jude and Tesar 1985, and Jude et al 1987. The chances of overstocking salmon increased since the alewife population was decreasing, and there was increasing evidence that salmon were reproducing (Trudeau 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since the closure of the commercial fishery in Lake Michigan in 1976, increased density-dependent growth appears to be occurring (Jude and Tesar, 1985;Brown et al, 1987;Brown and Eck, 1992). Skewed sex ratios of bloater (e.g., 80-90% females) have been hypothesized to have contributed to the decline of bloater populations in lakes Michigan and Huron from ∼1960 until 1975 Crowder, 1980;Jude and Tesar, 1985;Brown et al, 1987). The mechanism by which the skewed sex ratios occur in bloater has been hypothesized to be the result of a change in the neuroendocrine aspect of bloaters or a reduced viability of males (Philips and Ehlinger, 1995;Turgeon et al, 1999).…”
Section: Intraspecific Competitorsmentioning
confidence: 99%
“…Fish ecology of Laurentian Great Lakes nearshore zones has been the subject of comparatively few studies (e.g., Jude and Tesar 1985;Kelso and Minns 1996;Brazner and Beals 1997;Brazner 1997;Garza and Whitman 2004;Goforth and Carman 2005;Dopazo et al, 2008), especially in exposed shore areas (Randall and Minns 2002;Mackey and Goforth 2005). The few studies that exist suggest that biological communities can become altered along shorelines with high levels of anthropogenic activity compared to intact shorelines (e.g., Brazner 1997;Brazner and Beals 1997;Goforth and Carman 2005;Meadows et al, 2005).…”
Section: Discussionmentioning
confidence: 99%